2021
DOI: 10.1097/nnr.0000000000000555
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of Breastfeeding Effects for Infants With Neonatal Abstinence Syndrome

Abstract: Supplemental digital content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 47 publications
0
21
0
Order By: Relevance
“…Investigating the use of targeted nutritional immunological interventions (ie, provision of human milk and pre- and probiotic supplementation) may be a fundamental contribution to improve NOWS-related outcomes, specifically those related to GI dysfunction, via the gut microbiome 20. Given current evidence, nurses can promote the use of human milk as the optimal source of nutrition for infants with POE and NOWS 14…”
Section: Discussionmentioning
confidence: 99%
“…Investigating the use of targeted nutritional immunological interventions (ie, provision of human milk and pre- and probiotic supplementation) may be a fundamental contribution to improve NOWS-related outcomes, specifically those related to GI dysfunction, via the gut microbiome 20. Given current evidence, nurses can promote the use of human milk as the optimal source of nutrition for infants with POE and NOWS 14…”
Section: Discussionmentioning
confidence: 99%
“…Findings from a recent meta-analysis aimed at examining the effect of breastfeeding on NOWS-related outcomes suggest that breastfeeding improves the health outcomes for affected infants (Chu et al, 2022). Breastfeeding was found to be associated with decreased severity of NOWS symptoms, shorter duration of hospital stays, and reduced need for pharmacologic treatment in infants with NOWS (Chu et al, 2022). National guidelines exist encouraging the use of breastfeeding as an infant feeding method for childbearing women with OUD who are stable on medication treatment (American College of Obstetricians and Gynecologists [ACOG], 2017).…”
Section: Stigma and Childbearing Women With Oudmentioning
confidence: 99%
“…Findings from a recent meta-analysis aimed at examining the effect of breastfeeding on NOWS-related outcomes suggest that breastfeeding improves the health outcomes for affected infants (Chu et al, 2022). Breastfeeding was found to be associated with decreased severity of NOWS symptoms, shorter duration of hospital stays, and reduced need for pharmacologic treatment in infants with NOWS (Chu et al, 2022).…”
Section: Stigma and Childbearing Women With Oudmentioning
confidence: 99%
“…Although limited by small sample sizes, breastmilk analyses have shown that the concentrations of buprenorphine and methadone are low and pose minimal risks to neonates ( 31 , 32 ). There are clear benefits of breastfeeding including less severe withdrawal, less need for pharmacotherapy, and shorter length of hospital stay ( 33 , 34 ). The American Academy of Pediatrics (AAP) has recommended breastfeeding based on long-term benefits such as lower risk of type II diabetes, hypertension, and cancer in mothers and lower respiratory tract infections, diarrhea, otitis media, sudden infant death syndrome, asthma, and obesity in infants and children ( 28 ).…”
Section: Ongoing Management and Long-term Effects Of Nasmentioning
confidence: 99%